IMPROVED TEMPERATURE STABILITY IN SEDIMENTATION TANK WITH VEGETATION CANOPY - Marsono, Bowo Djoko; Mangkoedihardjo, Sarwoko (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2024)
Naturally the water temperature is correlated with the density and viscosity. Changes in temperature due to sunlight affect processes in water treatment such as sedimentation and coagulation. The detrimental effect is the presence of density currents on the surface during the day, thereby reducing the efficiency of particle sedimentation. Vegetation Canopy can be applied in sedimentation tanks to cope with changes in temperature on the surface of the water mass. This method can be implemented by planting trees around the tank in addition to fabric fiberglass. Tall trees and canopies with large leaves will cover the surface area of ​​the sedimentation tank so that changes in water temperature due to sunlight can be reduced. To apply this technique, submerged orifices and a net above the water surface are used at the outlet channel of the sedimentation basin.